Fencer`s perception of affordances of an opponent`s attack - Chen, Y.-H.; Liu, Y.-T. (International Journal of Sports Science & Coaching, 2018)
We investigated fencers` perception of affordances of the opponent by asking them to estimate the reach-ability (length of lunge) of the opponent that varied in height and moved toward them in different paces. Their task was to initiate a backward step at the moment that they perceived to be reached by the opponent in a lunge attack. All trials were recorded by a video camera for data digitizing process and analyses. The results revealed that the opponent`s approaching velocity, but not the opponent`s stature, influenced fencers` estimates, suggesting that action-related characteristics of the observed person were more influential on perceiver`s perception of affordances of the observed person. Moreover, fencers` perception of "time-to-contact by the opponent" changed as a function of the opponent`s velocity, suggesting that in the context of combat sports that time-to-contact could be a useful variable for the control of actions when interacting with a moving opponent.